Search for battleship Bismark - Prentice, Patrick; Schnall, Peter; Weber, Christine (The Society, 1989)
Reveals the remarkable footage on the undersea exploration of German's most powerful vessel, Bismarck. Dr. R.D. Ballard discovered the sunken WW II battleship, 600 miles off the coast of France on June 8, 1989 after almost half a century.